2001
DOI: 10.1111/1467-9515.00221
|View full text |Cite
|
Sign up to set email alerts
|

New Labour, Old Functionalism: The Underlying Contradictions of Welfare Reform in the US and the UK

Abstract: Through references to Hansard, official papers, Fabian pamphlets and pertinent texts from the fields of politics, sociology and social policy, this piece illustrates the similarities of thought behind the deliberations of New Labour and those of the early American functionalists and their modernday counterparts. Examination of the rhetoric used by both parties shows that there are three main focal points of comparison. On one level there is a shared belief in the cohesive impetus of realistic "aspiration" in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The 1.25 million people helped back into work since the New Deals began (Blair, 2002) are not to be dismissed lightly, but other evidence is less positive. Certain commentators have suggested that the New Deals may not be as successful as they at first appear and make strong arguments that industry and capital rather than unemployed people/lone parents are the real beneficiaries of the New Deals (Grover and Stewart, 2000;Gray, 2001;Prideaux, 2001). Peck (2001) A number of studies have noted the potential positive effects of policies that encourage lone parents into the paid labour market but simultaneously they have emphasised that the provision of quality support and education/training schemes and help with childcare are vitally important (Heron et al, 2002;Bradshaw, 1996).…”
Section: Access To Welfare Benefits Is One Side Of the Contract Betwementioning
confidence: 99%
See 2 more Smart Citations
“…The 1.25 million people helped back into work since the New Deals began (Blair, 2002) are not to be dismissed lightly, but other evidence is less positive. Certain commentators have suggested that the New Deals may not be as successful as they at first appear and make strong arguments that industry and capital rather than unemployed people/lone parents are the real beneficiaries of the New Deals (Grover and Stewart, 2000;Gray, 2001;Prideaux, 2001). Peck (2001) A number of studies have noted the potential positive effects of policies that encourage lone parents into the paid labour market but simultaneously they have emphasised that the provision of quality support and education/training schemes and help with childcare are vitally important (Heron et al, 2002;Bradshaw, 1996).…”
Section: Access To Welfare Benefits Is One Side Of the Contract Betwementioning
confidence: 99%
“…Indeed, the extent to which this principle underpins the British Government's general approach to welfare reform has been extensively commented upon (Deacon, 2002a;Dwyer, 2002Dwyer, , 2000Dwyer, , 1998Prideaux, 2001;Etzioni, 2000;Lister, 1998;Powell, 1999) 2 . Following this introduction, part one of the paper places the recent UK welfare reforms, which have a 'principle of conditionality' at their core, within a discussion of the wider emergence of 'active/Third Way' social policies in many Western welfare states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1.25 million people helped back into work since the New Deals began (Blair, 2002) are not to be dismissed lightly, but other evidence is less positive. Certain commentators have suggested that the New Deals may not be as successful as they at first appear and make strong arguments that industry and capital rather than unemployed people/lone parents are the real beneficiaries of the New Deals (Grover and Stewart, 2000;Gray, 2001;Prideaux, 2001). Peck (2001) also notes that job entry rates for the New Deal to March 2000 were modest, with overall only a third of participants leaving to enter paid work.…”
Section: Access To Welfare Benefits Is One Side Of the Contract Betwementioning
confidence: 99%
“…Taylor-Gooby, 2000;Dean, 2000). Welfare to work policies, so often identified as being of central importance, appear better at meeting the requirements of industry and capital rather than poor citizens (Peck, 2001;Prideaux, 2001).…”
Section: Conclusion: Positive Ways Forwardmentioning
confidence: 99%